Effects of Oxaliplatin on Facial Sensitivity to Cool Temperatures and TRPM8 Expressing Trigeminal Ganglion Neurons in Mice - Caudle, Robert M.; Neubert, John K. (Frontiers in Pain Research, 2022)
The chemotherapeutic agent oxaliplatin is commonly used to treat colorectal cancer. Although effective as a chemotherapeutic, it frequently produces painful peripheral neuropathies. These neuropathies can be divided into an acute sensitivity to cool temperatures in the mouth and face, and chronic neuropathic pain in the limbs. The chronic neuropathy also includes sensitivity to cool temperatures. Neurons that detect cool temperatures are reported to utilize Transient Receptor Potential Cation Channel, Subfamily M, Member 8 (TRPM8). Therefore, we investigated the effects of oxaliplatin on facial nociception to cool temperatures (18ºC) in mice and on TRPM8 expressing trigeminal ganglion (TRG) neurons. Paclitaxel, a chemotherapeutic that is used to treat breast cancer, was included for comparison because it produces neuropathies, but acute cool temperature sensitivity in the oral cavity or face is not typically reported. Behavioral testing of facial sensitivity to 18ºC indicated no hypersensitivity either acutely or chronically following either chemotherapeutic agent. However, whole cell voltage clamp experiments in TRPM8 expressing TRG neurons indicated that both oxaliplatin and paclitaxel increased Hyperpolarization-Activated Cyclic Nucleotide-Gated channel (HCN), voltage gated sodium channel (Nav), and menthol evoked TRPM8 currents. Voltage gated potassium channel (Kv) currents were not altered. Histological examination of TRPM8 fibers in the skin of the whisker pads demonstrated that the TRPM8 expressing axons and possible Merkel cell-neurite complexes were damaged by oxaliplatin. These findings indicate that oxaliplatin induces a rapid degeneration of TRG neuron axons that express TRPM8, which prevents evoked activation of the sensitized neurons and likely leads to reduced sensitivity to touch and cool temperatures. The changes in HCN, Nav, and TRPM8 currents suggest that spontaneous firing of action potentials may be increased in the deafferented neurons within the ganglion, possibly producing spontaneously induced cooling or nociceptive sensations.